Indonesian Religious Culture and the Undercurrent - Kumar, Gautam (Center for Research and Development of Religious Literature and Heritage, 2016)
Indonesia is known to the world not only for its multi religious ethos but for its unique cultural legacy, nurtured by its people who, as individuals, adhere to quite a wide variety of different faiths and beliefs. The author tries to give a narrative on those Indic elements in particular which have substantially influenced the social system of Indonesia. The paper deals with the historical perspective and how the present day Indonesian cultural system allows that the traditions of Ramayana, Mahabharata and other Indic folklore survive throughout the archipelago. It will also assess how the state’s patronage of these unique cultural traditions has made possible the preservation of these inexpensive customs which not only grant to the general mass a unique identity but also gives them a strong feeling of belonging to a common culture. The study establishes India’s strong cultural links with Indonesia by providing evidence of the deep route by which the oral traditions of mythological epics in Indonesia i.e. Ramayana and Mahabharata puppetry and also its dance forms (similar to the pattern of Ramleela in the northern part of India) came to be in the archipelago at all.